2011
DOI: 10.2514/1.50935
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Optimal Trajectories for Earth Hybrid Pole Sitters

Abstract: A pole-sitter orbit is a closed path that is constantly above one of the Earth's poles, by means of continuous low thrust. This work proposes to hybridize solar sail propulsion and solar electric propulsion (SEP) on the same spacecraft, to enable such a pole-sitter orbit. Locally-optimal control laws are found with a semi-analytical inverse method, starting from a trajectory that satisfies the pole-sitter condition in the Sun-Earth circular restricted three-body problem. These solutions are subsequently used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
(33 reference statements)
1
42
0
Order By: Relevance
“…While the hybrid propulsion pole-sitter can in principle enable a mission that is not feasible using only a solar sail and can extend the mission lifetime with respect to the pure SEP scenario, there are still issues associated with the polesitter mission related to the large distance from the Earth. As expected, the acceleration required increases dramatically as the spacecraft is stationed closer to the Earth, and reasonable values of acceleration are obtained only if the Earth-spacecraft distance is of the order of millions of kilometers [6,10]. Nevertheless, the advantage of having a static or quasi-static platform is such that these concepts are worth considering and investigating in more detailed studies [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the hybrid propulsion pole-sitter can in principle enable a mission that is not feasible using only a solar sail and can extend the mission lifetime with respect to the pure SEP scenario, there are still issues associated with the polesitter mission related to the large distance from the Earth. As expected, the acceleration required increases dramatically as the spacecraft is stationed closer to the Earth, and reasonable values of acceleration are obtained only if the Earth-spacecraft distance is of the order of millions of kilometers [6,10]. Nevertheless, the advantage of having a static or quasi-static platform is such that these concepts are worth considering and investigating in more detailed studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although high-bandwidth telecommunications and high-resolution imagery are difficult due to the large Earth-spacecraft distance, a number of novel potential applications are enabled, both in the fields of observation and telecommunications, which will be discussed in the paper. Due to these capabilities, and with the aim of increasing mission lifetime, the authors have undertaken an extensive investigation focused on the concept of a hybrid-propulsion pole-sitter: from the generation of optimal hybrid pole-sitter orbits [10], to system mass budgets [20], and from design of optimal transfers to the pole-sitter orbit from LEO [21], to design of optimal north-to-south transfers [22]. This paper presents the full mission and systems analysis of a pole-sitter mission, covering the launch phase and the operational phase.…”
Section: Introductionmentioning
confidence: 99%
“…It was in fact shown that the acceleration required increases dramatically when the spacecraft gets closer to the Earth, and reasonable values of acceleration are obtained only if the spacecraft is in the range of millions of kilometers from the Earth [5,13]. This means that these types of platforms will certainly not be used in the near future for high-bandwidth telecommunications and high-resolution imagery.…”
Section: Introductionmentioning
confidence: 99%
“…One of the intrinsic limitations of solar sailing is the relationship between the direction of the sail force vector and its magnitude; in particular, the force can never be directed towards the Sun, which is the reason why a sailcraft cannot maintain the pole-sitter position indefinitely [13]. In the effort of bypassing the limitations of SEP and solar sailing, a hybridization of these systems was proposed [14].…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years the opportunities that solar sails provide in terms of highly non-Keplerian behavior, with applications such as displaced orbits [2] and polar loitering [3], have come to be recognized, and attractive concepts such as orbit raising from low Earth orbit [4] and inclination change [5] have been proposed. To achieve these objectives, some form of control over the direction and magnitude of the thrust produced by the solar sail has usually been required [6].…”
Section: Introductionmentioning
confidence: 99%